The Martyrdom of Polycarp : Translation, Introduction, and Commentary - Croy, N. Clayton (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026., 2026)
This volume provides a detailed introduction addressing critical issues such as authorship, date, integrity, miracles, Jewish involvement, the imitation of Christ, theology, and ethics. The section-by-section commentary examines grammar, philology, text critical questions, metaphors, intertextuality, historical issues, etc. In addition, there are numerous excursuses on topics such as the charge of atheism in antiquity, praying toward the east, the repurposing of Roman stadia, and the cult of the saints. Throughout, the author engages a wide array of secondary literature. A modern theological postscript considers the ongoing relevance of the Martyrdom of Polycarp in our contemporary world marked by religious violence